Aerobic Plate Count of Contaminants and Molecular Characterization of Eschereichia Coli in Raw Chicken Meat in Ismailia, Egypt - A. Afify, El-Sayed; A Shaltout, Fahim; I. M, Zakaria, (Journal of Veterinary Healthcare, 2020)
A total number of 100 samples from ten random broiler chicken carcasses (breast and thigh) were collected from an automatic poultry slaughtering plant in Ismailia city, Egypt. The mean values of Enterobacteriacae count were 5.9x104±9.7x103 cfu/g and 7.1x 104 ± 1.1x104 cfu/g for chicken breast and thigh samples respectively. The prevalence of E.coli were 12% and 9% breast and thigh samples examined, respectively. They are serologically identified as 33.35 and 22.2% O157:H7 (EHEC) , 16.6% and 11.1% O114:H21(EPEC), 16.6% and 33.3 %O127:H6 (ETEC) , 0% and 0% O126 (ETEC) and 33.3% and 0% O26 (EHEC) for breast and thigh samples, respectively. The incidence of E.coli O157:H7 was 100% in both serological and PCR methods from biochemical positive E.coli samples. Culture is specific and cheap whereas PCR is sensitive and expensive, hence, we recommend both culture and molecular methods, which improve sensitivity and specificity, to enhance detection of foodborne pathogens including E.coli.
Keywords: Chicken meat; Identification; characterization; E.coli; PCR